O golpe civil-militar de 1964 no Jornal Tribuna de Itararé: a imprensa como fonte para o Ensino de História - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
The 1964 Civil-Military Coup is a recent event in the Brazilian history which, even after more than fifty years, still gives rise to narrative disputes. In recent years, the revision of the theme has been appropriated by revisionist groups that intend to offer “another version” of this episode. The deposition of President João Goulart had the support from different sectors of Brazilian society, including the official press. In the present work, our main goal is investigating how the newspaper Tribuna de Itararé, from the city of Itararé-SP, positioned itself in face of the Brazilian political crisis of the 1960s and the dispute between two models of society (capitalism and communism), an escalation that contributed to the coup d’état, and presenting a proposal for the use of this source in History Teaching. We selected publications of the newspaper from early 1960 until 1964, as well as the memory built by the newspaper about its own past. We also turned our attention to the 1964 coup’s historiography while prioritizing research which used the press as a source. The methodology used in the research was the analysis of content, from Bardin (2006) and the concepts used were those of representations, based on Moscovici (2007) and Jodelet (2012), and memory, according to Nora (1993) and Pollak (1989). As a result, we offer a book of sources with methodological suggestions and activities to be used by History teachers during their classes. In this way, we intend to contribute to the valorization of local history and to a history teaching that is critical and resistant to anti-democratic ideas which surround our society.
Keywords: Golpe de 1964; Ensino de História; Tribuna de Itararé; Imprensa; Representações; 1964 Coup; Teaching History; Tribuna de Itararé; Press; Representations; CNPQ::CIENCIAS HUMANAS::HISTORIA